Sequence, structural and evolutionary relationships between class 2 aminoacyl-tRNA synthetases. - Cusack, S (1991)
Class 2 aminoacyl-tRNA synthetases, which include the enzymes for alanine, aspartic acid, asparagine, glycine, histidine, lysine, phenylalanine, proline, serine and threonine, are characterised by three distinct sequence motifs 1,2 and 3 (reference 1). The structural and evolutionary relatedness of these ten enzymes are examined using alignments of primary sequences from prokaryotic and eukaryotic sources and the known three dimensional structure of seryl-tRNA synthetase from E. coli. It is shown that motif 1 forms part of the dimer interface of seryl-tRNA synthetase and motifs 2 and 3 part of the putative active site. It is further shown that the seven alpha 2 dimeric synthetases can be subdivided into class 2a (proline, threonine, histidine and serine) and class 2b (aspartic acid, asparagine and lysine), each subclass sharing several important characteristic sequence motifs in addition to those characteristic of class 2 enzymes in general. The alpha 2 beta 2 tetrameric enzymes (for glycine and phenylalanine) show certain special features in common as well as some of the class 2b motifs. In the alanyl-tRNA synthetase only motif 3 and possibly motif 2 can be identified. The sequence alignments suggest that the catalytic domain of other class 2 synthetases should resemble the antiparallel domain found in seryl-tRNA synthetase. Predictions are made about the sequence location of certain important helices and beta-strands in this domain as well as suggestions concerning which residues are important in ATP and amino acid binding. Strong homologies are found in the N-terminal extensions of class 2b synthetases and in the C-terminal extensions of class 2a synthetases suggesting that these putative tRNA binding domains have been added at a later stage in evolution to the catalytic domain.